1996
DOI: 10.1111/j.1365-3156.1996.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Og4C3 ELISA in Wuchereria bancrofti infection: infected persons with undetectable or ultra‐low microfilarial densities

Abstract: The recently developed O g 4 c 3 ELISA, which detects circulating Wuchereria bancrofti antigen, appears promising for use in epidemiological surveys, but its sensitivity is unknown in persons with ultra-low microfilarial densities. We used the O g q c 3 to test the sera of 282 persons who were microfilaria-positive in 1-16 ml of blood, 18 persons who were microfilaria-negative but who had ultrasonographic or biopsy evidence of adult W. bancrofti infection, and 63 lifelong residents of a non-endemic area of Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 11 publications
3
35
1
1
Order By: Relevance
“…Considering the non-endemic normals and microfilaria carriers, the Og4C3-ELISA test was found to have 100 % sensitivity and 94.12 % specificity for detection of Mf carriers in sera samples. Comparison of finger prick dried blood spots (DBS) and sera samples by ELISA vis-à-vis the immunochromatographic test (ICT), carried out on Mf carriers (n = 91) and endemic normals (n = 97), showed a positivity of 88 (96.7 %) in DBS as against 86 (94.5 %) in sera samples and 88 (96.7 %) by ICT, amongst Mf carriers, with a statistically significant correlation in antigen units between sera and DBS samples (r = 0.959, p = 0.000) amongst the microfilaria carriers (Rocha et al 1996). But it is cost prohibitive for field use.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Considering the non-endemic normals and microfilaria carriers, the Og4C3-ELISA test was found to have 100 % sensitivity and 94.12 % specificity for detection of Mf carriers in sera samples. Comparison of finger prick dried blood spots (DBS) and sera samples by ELISA vis-à-vis the immunochromatographic test (ICT), carried out on Mf carriers (n = 91) and endemic normals (n = 97), showed a positivity of 88 (96.7 %) in DBS as against 86 (94.5 %) in sera samples and 88 (96.7 %) by ICT, amongst Mf carriers, with a statistically significant correlation in antigen units between sera and DBS samples (r = 0.959, p = 0.000) amongst the microfilaria carriers (Rocha et al 1996). But it is cost prohibitive for field use.…”
Section: Discussionmentioning
confidence: 94%
“…Antigen tests are more sensitive (Lammie et al 1994) and are used to assess the situation (Bal et al 2009;Das et al 2005;Melrose et al 2000;Nuchprayoon et al 2001;Shah and Mulla 2007;Steel and Ottesen 2001;Tisch et al 2001;Weerasooriya et al 2002) in different endemic countries. Antigen tests were also used to evaluate other methods of detection (Rocha et al 1996;Wattal et al 2007). Considering the non-endemic normals and microfilaria carriers, the Og4C3-ELISA test was found to have 100 % sensitivity and 94.12 % specificity for detection of Mf carriers in sera samples.…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows for the identification of W. bancrofti antigens in serum, plasma and hydrocele fluid and does not show any cross-reactivity with other helminthic infections (More & Copeman 1990, Rocha et al 1996, TropBIO 1996, Rocha 2004.…”
Section: Lymphatic Filariasis (Lf) Is a Parasitic Disease Caused By Nmentioning
confidence: 99%
“…1,9 Though it is impossible to accurately determine the number of macrofilariae in vivo, this assertion is supported by studies that have shown a relationship between antigen levels and microfilarial densities in mf-positive individuals before treatment, 1,[15][16][17][18][19][20][21][22] and a relationship between antigen levels and microfilarial densities with the frequency of detection of worm nests by ultrasonography. [10][11][12]16,23 The original AD12 ELISA and the Og4C3-based TropBio ELISA tests are useful for quantitating filarial antigenemia.…”
mentioning
confidence: 95%